I'm trying to evaluate $$\lim_{n\to+\infty} \prod_{k=1}^{n} \frac{2k}{2k+1}$$ First I notice that since $k\geq1$ it is $\frac{2k}{2k+1}>0$ for all $k\in\{1,...,n\}$; so $$0\leq\lim_{n\to+\infty} \prod_{k=1}^{n} \frac{2k}{2k+1}$$ Then I notice that $$\prod_{k=1}^{n} \frac{2k}{2k+1}=\exp{\ln\left(\prod_{k=1}^{n} \frac{2k}{2k+1}\right)}=\exp{\sum_{k=1}^{n}\ln\left(\frac{2k}{2k+1}\right)}=$$ $$=\exp{\sum_{k=1}^{n}\ln\left(1-\frac{1}{2k+1}\right)}$$ Since $\ln(1+x)\leq x$ for all $x>-1$ and since $\exp$ is an increasing function it follows that $$\exp{\sum_{k=1}^{n}\ln\left(1-\frac{1}{2k+1}\right)}\leq\exp{\sum_{k=1}^{n}-\frac{1}{2k+1}}$$ So $$\lim_{n\to+\infty}\prod_{k=1}^{n} \frac{2k}{2k+1}\leq\lim_{n\to+\infty}\exp{\sum_{k=1}^{n}-\frac{1}{2k+1}}$$ Since $\exp$ is a continuous function it follows that $$\lim_{n\to+\infty}\exp{\sum_{k=1}^{n}-\frac{1}{2k+1}}=\exp{\sum_{k=1}^{+\infty}-\frac{1}{2k+1}}=e^{-\infty}=0$$ So by the comparison test we deduce that the limit is $0$.

Is this correct? Thanks for your time.

  • 1
    $\begingroup$ Yes your derivation is correct. +1 $\endgroup$ – Paramanand Singh Feb 9 at 14:13
  • 1
    $\begingroup$ I understand what $e^{-\infty}$ is supposed to represent, but I don't consider it particularly good style. I would write $$\exp \sum _{k=1}^n -\frac{1}{2k+1} \xrightarrow[n\to\infty]{}0 $$ But that's just a minor detail. +1 $\endgroup$ – Alvin Lepik Feb 9 at 14:24
  • 1
    $\begingroup$ In an infinite product like this, we say that it "diverges to zero". See math.stackexchange.com/q/3513417/442 $\endgroup$ – GEdgar Feb 9 at 14:40
  • 1
    $\begingroup$ Using the mathematical induction method it can be shown that the respective string is smaller than $\frac{1}{(n+1)^\frac{1}{2}}$. $\endgroup$ – medicu Feb 9 at 16:17

Another way:

Using arithmetic geometric Inequality

$$\frac{k+k-1}{2}> \sqrt{k\cdot(k-1)}\Rightarrow \frac{2k-1}{2k}>\sqrt{\frac{k-1}{k}}$$

$$\frac{2k}{2k-1}<\sqrt{\frac{k-1}{k}}\Rightarrow \prod^{n+1}_{k=2}\frac{2k}{2k-1}<\prod^{n+1}_{k=2}\sqrt{\frac{k-1}{k}}=.\frac{1}{\sqrt{n+1}}$$

$$\Longrightarrow 0<\prod^{n+1}_{k=2}\frac{2k}{2k-1}<\frac{1}{\sqrt{n+1}}$$

Applying limit $n\rightarrow \infty$ and Using Squeeze Theorem

We have $$\prod^{n+1}_{k=2}\frac{2k}{2k-1}=0$$

  • 1
    $\begingroup$ The second line is incorrect: The first inequality should be $\frac{2k}{2k-1} < \sqrt{\frac{k}{k-1}}$. Consequently, several other statements are incorrect. $\endgroup$ – PolyaPal yesterday

Your caclulations are correct.

But I thought it might be interesting to see another nice trick.

  • Let $A_n = \prod_{k=1}^n\frac{2k}{2k+1}$ and $B_n = \prod_{k=1}^n\frac{2k+1}{2k+2}$.

Then, $A_n < B_n$ and $A_nB_n$ is a telescoping product and you get

$$A_n^2 < A_nB_n = \frac{2}{2n+2}=\frac 1{n+1}$$


$$0 < A_n < \frac{1}{\sqrt{n+1}}\stackrel{n\to \infty}{\longrightarrow}0$$


Yours is fine. Another simple method would be $$\lim_{n\to\infty}\prod_{k=1}^n\dfrac{2k}{2k+1}<\lim_{n\to\infty}\prod_{k=1}^n\dfrac{2k}{2k+2}\\ = \lim_{n\to\infty}\dfrac{1}{n+1}\\=0$$


As Dr.WolfgangHintze pointed out in the comments, this inequality is in the reverse direction, so now we have the rate of decay of this series (from other answers). $$\dfrac{1}{\sqrt{n+1}}>\prod_{k=1}^n\dfrac{2k}{2k+1}>\dfrac{1}{n+1}$$

  • $\begingroup$ @ Martund Looks nice, but, unfortunately, your inequality is wrong. $\endgroup$ – Dr. Wolfgang Hintze Feb 13 at 8:32
  • $\begingroup$ @Dr.WolfgangHintze, Why do you think that is wrong? $\endgroup$ – Martund Feb 13 at 18:24
  • $\begingroup$ Because $\frac{2k}{2k+1} > \frac{2k}{2k+2}$ and not $\lt$ $\endgroup$ – Dr. Wolfgang Hintze Feb 13 at 19:21
  • $\begingroup$ @ Martund I'm glad you could save your reasoning. Just a remark: for $n\ge2$ you can write your inequality even more elegant as $\frac{1}{\sqrt{n}}\gt \prod_{k=1}^n \frac{2k}{2k+1} \gt \frac{1}{n}$ $\endgroup$ – Dr. Wolfgang Hintze Feb 14 at 8:59

Consider $$a_n=\prod_{k=1}^{n} \frac{2k}{2k+1}\implies \log(a_n)=\sum_{k=1}^{n}\log \left(\frac{2 k}{2 k+1}\right)=-\sum_{k=1}^{n}\log \left(1+\frac{1}{2 k}\right) $$ Use Taylor expansion $$\log \left(1+\frac{1}{2 k}\right)=\frac{1}{2 k}-\frac{1}{8 k^2}+O\left(\frac{1}{k^3}\right)$$ Compute the sum for this truncated series to get $$\log(a_n)\sim-\frac{H_n}{2}+\frac{H_n^{(2)}}{8}$$ where appear generalized harmonic numbers.

Use the asymptotics for large $n$ to get $$\log(a_n) =\left(\frac{\pi ^2}{48}-\frac{\gamma }{2}\right)-\frac{1}{2} \log \left({n}\right)-\frac{3}{8 n}+O\left(\frac{1}{n^2}\right)$$

$$a_n\sim \frac{ \exp\left(\frac{\pi ^2}{48}-\frac{\gamma }{2}\right)}{\sqrt n}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.